Analisis Vegetasi Tumbuhan Bawah di Kawasan Geopark Silokek Kabupaten Sijunjung - Kamelia Putri M. Nur; Chairul Chairul (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Research on the analysis of undergrowth vegetation in the Silokek Geopark Area, Sijunjung Regency. This study aims to determine the composition and structure of the undergrowth in the Silokek Geopark Area, Sijunjung Regency. Vegetation analysis was carried out by using the transect method and purposive sampling by placing plots on the right and left of the transect, with a plot size of 2x2 m. There are 10 plots were created and species identification was carried out at the Andalas University Herbarium. Based on the results of the study, 12 families, 15 genera, 15 species, and 103 individuals were found with the dominant family being Poaceae and the co-dominant families Asteraceae, Schizaeceae, and Selaginellaceae. The highest important value index of Lygodium circinnatum is 30.79%. Understorey diversity index of 2.57. Based on the research, it can be concluded that the Poaceae family is able to reproduce well in this location and the diversity of understoreys is classified as moderate. It is recommended that local governments and local communities protect the biodiversity in this area.